Comparison of Mineral Density in Molar Incisor Hypomineralization applying fluoride varnishes and casein phosphopeptide-amorphous calcium phosphate - Biondi, Ana Maria (2017)
The aim of the present work was to evaluate and comparevariations in mineral density (MD) using laserinducedfluorescence (LF) after applying 5% Sodium Fluoride Varnish(Duraphat®), 5% Sodium Fluoride Varnish with TricalciumPhosphate (Clinpro®) or Casein phosphopeptideamorphouscalcium phosphate (Recaldent®) on teeth with Molar IncisorHypomineralization (MIH). Mineral density of 92 MIH teethwith mild (Mi) and moderate (Mo) lesions was assessed using aDIAGNOdent device (KaVo, Biberach, Germany). LF valueswere recorded on day 0 (baseline) and on days 15, 30 and 45;the remineralizing agents were applied immediately after LFreadings at baseline and on days 15 and 30. Data correspondingto Mi and Mo lesions were analyzed separately. Significantdifferences were observed both in mild (p<0.01) and moderate(p<0.000005) lesions. Differences between Recaldent® andClinpro®, and between Duraphat® and Clinpro® (global level0.10) were found in Mi lesions. All 3 pairs of products differedsignificantly in Mo lesions (global level 0.05). The resultsobtained under the conditions used here allow concluding thatClinpro® was more effective in mild lesions whereas Duraphat®was more effective in moderate lesions.Key words: Dental enamel, dental enamel hypoplasia, lasers.